The other side of the K-pop phenomenon - Escobar-Fuentes, Silvia; Montalbán-Peregrín, Francisco Manuel (My University, 2022)
K-pop is understood as pop music produced exclusively in South Korea. This musical genre emerged in the 1990s in that country (Navarro Hernández, 2020). However, after its success, the reproduction of sexism is hidden both in its lyrics, outfits and in its choreographies and, in addition, it can be seen how K-pop reflects of the most traditional Korean culture and its representation today. Authors such as Lin and Rudolf (2017) state that K-pop stands out for the sexualization of its content and putting lookism in the spotlight. According to this research work, Kim (2016) reports that women in K-pop are divided into two categories: (1) active women and (2) passive women. This is also transferred to public interventions in various media. Regarding the choreographies, Chuyun Oh (2014) shows that the choreographies reproduce the traditional gender ideology, since women dance sexually, fulfill "a patriarchal fantasy of femininity" and cover a small space, while men use more space and tend to do more stunts, flips and b-boying moves. In this line, Olmedo Señor (2017) emphasizes that the female groups where choreographies more related to hip hop are carried out and use more acrobatics do not like the public as much or do not even become mainstream. In this sense, women are more susceptible to being sexually objectified and conditioned to stricter beauty standards. After these arguments, in this work 20 successful K-pop songs have been analysed, focusing on messages related to sexism, gender imagery, interpersonal relationships, etc., and their relationship with Korean culture. All this under a qualitative methodology, based on discourse analysis (Potter and Wetherell, 1997) that seeks to detect interpretative repertoires on how gender identities are constructed.
Keywords: Música - Corea - Congresos; Corea - Cultura popular - Congresos; Conducta sexual en la música - Corea - Congresos; Sexismo - Corea - Congresos; Music; K-pop; Sexism; Korean culture